INTERGENERATIONAL FOOD TABOO: EXPLORATION THE FORMATION OF SELF-EFFICACY IN MOTHERS - Mutaqin, Moh Fikri Tanzil; Risna, Inten; Kurnaedi, Nedi; Rijkiah, Dinu; Juniarti, Depi Sari (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
Self-efficacy presents high confidence in achieving goals, including those who are pregnant. On the other hand, there is a food taboo phenomenon that is believed by people across generations in various regions including on the coast amidst the acceleration of information. This phenomenon is by carrying out food taboos that are believed to affect health. On the other hand, these taboos risk a person lacking nutritious food. Where other risks are the health of the fetus and child in the future and the risk of stunting. This manuscript will contain the main findings about the perspective of food taboo and the dynamics of their self-efficacy while continuing the legacy of food taboo from the previous generation. This study uses a qualitative approach, as many as 12 mothers on the coast were selected as respondents purposively to explore their food taboo perspective, with guidelines for food taboo and self-efficacy interviews. The analysis was carried out by coding through Nvivo, to then produce the main theme. The themes as findings in this study are related to 1) Effort Towards Goal with sub-sequence (Curiosity about health literacy, Focus on pregnancy, Food taboo is a problem, Taboos Are Just Myths), 2) Lack of Self-Efficay with sub-sequence (Belief in food taboos, Lack of literacy), 3) Social Persuasion with sub-sequence (cross-generational influences, individual beliefs).